ANALISIS FINANSIAL USAHATANI JAGUNG DAN TUMPANG SARI SISTEM JAJAR LEGOWO JAGUNG-KEDELAI DI KABUPATEN SELUMA - Astuti, Herlena Bidi; Hartono, Rudi; Rambe, Sri Suryani (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2019)
Corn-SoybeanJajar legowoisone way to maximize an agricultural land productivity with limited land and cost conditions. The purpose of this study was to estimatethe profitability and feasibility of corn monoculture farming and legowointercropping system of corn -soybean system in Seluma District. Survey of 28 cornmonoculture and4 corn-soybeanLegowo system were conducted to collect data on cost and production incurred in their farming activities.. The results of this study indicate that costs incurred by farmers who apply the jajar legowo corn -soybean system increase from Rp. 7,810,000 to Rp. 10,662,490. However, the difference in costs incurred is followed by differences in income or profits from farming, i.e.,Rp. 6,189,333 for corn farming and Rp. 11,848,510 for corn-soybean jajarlegowointercropping–system. Corn-soybean legowo is relativelyefficient with a B / C ratio of 1.83